Efficacy of Ketogenic Diet Again Re-Visited - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
A prospective multicenter study of the efficacy of the ketogenic diet in treatment of 51 children with intractable seizures is reported from 6 large institutions, including Johns Hopkins, Montefiore and Boston, USA, and Halifax, Canada, and 1 private practice setting.